Hallucinations: New Interventions Supporting People with Distressing Voices and/or Visions - Mark Hayward (Frontiers Research Topics, 2016)
Hallucinations can occur across the five sensory modalities (auditory, visual, olfactory, tactile, and gustatory). Whilst they have the potential to be benign or even highly valued, they can often be devastating experiences associated with distress, impaired social and occupational functioning, self-harm and suicide. Those who experience hallucinations in this latter manner may do so within the context of a wide range of psychiatric diagnoses, including schizophrenia, bipolar disorder, borderline personality disorder, and post-traumatic stress disorder. The only routinely available interventions for people distressed by hallucinations are antipsychotic drugs, which date from the introduction of chlorpromazine in the 1950s, and manualized cognitive behavioral therapy, which originated in the 1990s. These interventions do not help all people distressed by hallucinations, and in the case of antipsychotic medication, come with notable side-effects. There has hence been great interest in new interventions to support people distressed by hallucinations. The goal of this Frontiers Research Topic is to present a collection of papers on new developments in clinical interventions for those distressed by hallucinations. In the psychiatric condition that remains most strongly associated with hallucinations, schizophrenia, the majority (~70%) of people will have experienced hallucinations in the auditory modality, approximately a third will have experienced visual hallucinations, and a smaller minority will have experienced hallucinations in other modalities. Consistent with this prevalence, this collection focusses on auditory and visual hallucinations. This is not to minimise the potential distress that can occur from hallucinations in other modalities. For example, tactile hallucinations, particularly when stemming from earlier experiences of sexual abuse, can be highly distressing, and improved ways to help sufferers of such experiences are also needed. In summary, this collection aims to result in an interdisciplinary collection of papers which will appeal to a wide readership, spanning all with an interest in this area.